A SYSTEMATIC REVIEW ON DROPOUT OF INFERTILITY TREATMENTS AND RELATED FACTORS - Ratu Alicia, Dea Nabila (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Infertility occurs when a couple has been unable to produce a child for a period of at least one year while engaging in regular sexual activity and not using any kind of birth control. In addition, the pair must not have used any form of contraception during that time period. Fecundity is defined as a woman's ability to carry a pregnancy to full term without experiencing complications. Studies conducted on populations indicate that the probability of a woman becoming pregnant at any given month ranges between 20 and 25 percent overall. It is difficult to compare dropout rates across different facilities and nations due to factors such as the expense of infertility treatments, the regulations that control payment, and the accessibility of these therapies. The overwhelming majority of fertility specialists are obsessed with the outcomes of therapy and the success rates of their patients, but they frequently ignore or forget about the "invisible" individuals who withdraw from treatment. There is a lack of clarity regarding the causes and factors that lead individuals to quit focusing on their relationships. Many married couples find that they are better off financially if they choose to forego having any more children. During the period of mourning that is linked with an inability to produce children, undergoing at least one cycle of in vitro fertilization (IVF) may be performed as a "ritual." Several studies have found a correlation between dropout and a number of factors, some of which are as follows: emotional factors, communication issues, delaying treatment, physical and psychological burden, personal problems, refusal to accept treatment, problems related to the infertility organization and clinics, marital issues, age of women, number of previous births, previous unsuccessful treatments, poor treatment prognosis, child adoption, spontaneous pregnancy, and lack of insurance coverage are among the factors that have been found.